2017
DOI: 10.1038/cddis.2017.484
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA SNHG20 promotes non-small cell lung cancer cell proliferation and migration by epigenetically silencing of P21 expression

Abstract: Mounting evidence demonstrates that long non-coding RNAs (lncRNAs) are novel transcripts governing multiple biological processes, and their dysregulation is involved in the development and progression of multiple types of cancers. Small Nucleolar RNA Host Gene 20 (SNHG20) is a 2183 bp lncRNA, and its overexpression predicts poor prognosis in colorectal cancer and hepatocellular carcinoma. However, the clinical relevance of SNHG20 and its molecular mechanisms affecting cancer cell phenotype have not been docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 36 publications
3
87
0
Order By: Relevance
“…Existing evidence indicates that long noncoding RNAs (lncRNAs) are involved in the occurrence and development of liver diseases including NAFLD and HCC . Small nucleolar RNA host gene 20 (SNHG20) is a recently discovered lncRNA implicated in multiple cancers . Our preliminary results confirmed that SNHG20 expression was increased in liver tissues in the NALFD‐HCC (NALFD accompanied by HCC) tumor group compared with the NALFD group, both in human and experimental mouse livers.…”
Section: Introductionsupporting
confidence: 71%
“…Existing evidence indicates that long noncoding RNAs (lncRNAs) are involved in the occurrence and development of liver diseases including NAFLD and HCC . Small nucleolar RNA host gene 20 (SNHG20) is a recently discovered lncRNA implicated in multiple cancers . Our preliminary results confirmed that SNHG20 expression was increased in liver tissues in the NALFD‐HCC (NALFD accompanied by HCC) tumor group compared with the NALFD group, both in human and experimental mouse livers.…”
Section: Introductionsupporting
confidence: 71%
“…Then, Liu et al further presented evidence that levels of SNHG20 expression were increased in 96 pairs of hepatocellular carcinoma tissues and four cancer cell lines compared with adjacent normal tissues and normal human liver cell line, respectively . Moreover, Chen et al reported that SNHG20 expression was elevated in non‐small cell lung cancer samples compared with normal samples . In colorectal cancer, Li et al indicated that levels of SNHG20 expression were up‐regulated in tumor tissues compared to corresponding normal tissues from 107 .…”
Section: Discussionmentioning
confidence: 99%
“…In order to further explore the clinical significance of SNHG20 in the progression of osteosarcoma, we assessed the association between SNHG20 expression and clinical parameters of osteosarcoma cases, and observed high‐expression of SNHG20 was obviously associated with Enneking stage, distant metastasis, and histological grade. In non‐small cell lung cancer patients, Chen et al indicated levels of SNHG20 were correlated with advanced TNM stage and big tumor size . Moreover, Guo et al demonstrated that SNHG20 overexpression was related to bigger tumor size, advanced FIGO stage, and existent lymph node metastasis in patients with cervical cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that lncRNAs could bind to EZH2 and epigenetically silence the downstream target genes [26,28]. We therefore performed RNA immunopreciptation (RIP) analysis to examine whether SNHG6 could bind to EZH2.…”
Section: Snhg6 Inhibits P21 Expression In Colorectal Cancer Cellsmentioning
confidence: 99%